A brief review of drug discovery research for Human African Trypanosomiasis - Cullen, Danica; Mocerino, Mauro (Bentham Science Publishers, 2017)
Human African Trypanosomiasis (HAT), a neglected disease endemic in Sub-Saharan Africa, is usually fatal if left untreated. It is caused by the parasite Trypanosoma brucei, and is spread by the tsetse fly. The drugs currently available to treat HAT are few, and limited in efficacy. Furthermore, resistance towards these drugs is beginning to grow. In the last 25 years only one advance has been made into HAT treatment and consequently, there is an increasing need for new drugs to be sought that are able to effectively treat this disease. This review provides a brief overview of drug discovery research for HAT, focusing on research published in the last four years, identifying new molecules with the potential to be developed into anti-HAT agents. The methods of drug discovery have been grouped into three key areas; new molecules inspired by known antitrypanosomal agents, target-based screening, and phenotypic screening.